Description, microhabitat selection and infection patterns of sealworm larvae (Pseudoterranova decipiens species complex, nematoda: ascaridoidea) in fishes from Patagonia, Argentina - Hernández Orts, Jesús Servando (2013)
Third-stage larvae of the Pseudoterranova decipiens species complex (also known as sealworms) have been reported in at least 40 marine fish species belonging to 21 families and 10 orders along the South American coast. Sealworms are a cause for concern because they can infect humans who consume raw or undercooked fish. However, despite their economic and zoonotic importance, morphological and molecular characterization of species of Pseudoterranova in South America is still scarce. Methods: A total of 542 individual fish from 20 species from the Patagonian coast of Argentina were examined for sealworms. The body cavity, the muscles, internal organs, and the mesenteries were examined to detect nematodes. Sealworm larvae were removed from their capsules and fixed in 70% ethanol. For molecular identification, partial fragments of the mitochondrial cytochrome c oxidase subunit 1 gene (cox1) were amplified for 10 isolates from 4 fish species. Morphological and morphometric data of sealworms were also obtained. Results: A total of 635 larvae were collected from 12 fish species. The most infected fish was Prionotus nudigula, followed by Percophis brasiliensis, Acanthistius patachonicus, Paralichthys isosceles, and Pseudopercis semifasciata. Sequences obtained for the cox1 of sealworms from A. patachonicus, P. isosceles, P. brasiliensis and P. nudigula formed a reciprocally monophyletic lineage with published sequences of adult specimens of Pseudoterranova cattani from the South American sea lion Otaria flavescens, and distinct from the remaining 5 species of Pseudoterranova. A morphological description, including drawings and scanning electron microscopy photomicrographs of these larvae is provided. Sealworms collected from Argentinean fishes did not differ in their diagnostic traits from the previously described larvae of P. cattani. However a discriminant analysis suggests that specimens from P. nudigula were significantly larger than those from other fishes. Most of the sealworms were collected encapsulated from the muscles and, to a lesser degree, from the mesenteries and the liver. Conclusions: We provided the first molecular identification, morphological description and microhabitat characterization of sealworm larvae from the Argentinean Patagonian coast. We also reported the infection levels of sealworms on 20 fish species in order to elucidate the life cycle of these nematodes in this area.